Recent developments in Finnish mathematics education - Kupari, Pekka (NOMAD Nordic Studies in Mathematics Education, 2004)
The article addresses some development trends that have taken place in mathematics education of the Finnish comprehensive school over the past 15 years. A particular reason for such analysis arises from the international large-scale assessments on science and mathematics conducted at the turn of the millennium, which showed that Finnish student performance in mathematics is of a high international standard. Good achievement is attributable to a whole network of interrelated factors. The comprehensive school system seems to be successful in providing the majority of its students with a solid foundation for further schooling and for transition to working life. Long-term curricular measures and extensive development schemes have served as important framing factors. Also the high standard of teacher preparation and mathematics teachers’ professional skills is a factor that probably contributes to student performance. At the level of students, self-confidence in learning mathematics seems to be closely related to the level of performance. As regards remedies to shortcomings and problems, recognition of national strengths creates a positive atmosphere for improvement.